Impact of Environmental Concern and Awareness on Passengers' Intentions to Participate in Carbon Offset Schemes in Aviation: The Mediating Role of Attitude - Özcan, C; Öztürk, O (My University)
This study investigates the influence of Environmental Concern (EC) and Awareness of Consequences (AC) on passengers' Intentions to Participate in Carbon Offset Schemes (IPCOS) in aviation, with particular emphasis on the mediating role of Attitude (ATT). The research hypotheses were assessed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with the measurement and structural models evaluated using Smart-PLS 4 software. The findings indicate that AC has a direct and positive effect on both ATT and IPCOS. In contrast, EC does not directly influence IPCOS, suggesting that concern alone is insufficient to drive participation without presence of a positive ATT. The results confirm that ATT plays a crucial mediating role in the relationships between both EC and IPCOS, as well as AC and IPCOS. To enhance participation rates, policymakers should focus on increasing public awareness through targeted campaigns that highlight the environmental benefits and ethical dimensions of carbon offset schemes.
Keywords: environmental concern; attitudes; awareness; carbon offset scheme